Differential range use between age classes of southern African Bearded Vultures Gypaetus barbatus. - Sonja Krüger (PLoS ONE, 2014)
Bearded Vulture Gypaetus barbatus movements were investigated in southern Africa to determine whether an individual's age, sex or breeding status influenced its ranging behaviour and to provide the information required to guide conservation activities. Data from satellite transmitters fitted to 18 individuals of four age classes were used to determine range size and use. Because of the nature of the movements of marked individuals, these data could be used to determine the overall foraging range of the entire population, which was estimated to be 51 767 km(2). Although juvenile, immature and sub-adult birds used different parts of the overall range, their combined foraging range was 65% (33 636 km(2)) of the overall range. Average adult home ranges (286 km(2)) were only around 1% the size of the average foraging ranges of non-adults (10 540 -25 985 km(2)), with those of breeding adults being even smaller (95 km(2)). Home ranges of breeding adults did not vary in size between seasons but adults utilized their home range more intensively whilst breeding, moving greater distances during the incubation and chick hatching period. Range size and use increased as non-adults aged. Immatures and sub-adults had larger range sizes during winter, but range use of non-adults did not vary seasonally. Range size and use did not differ between the sexes in any of the age classes. Information on home range size and use enables specific areas within the species' range to be targeted for management planning, education and conservation action.